2019
DOI: 10.1136/bmjopen-2019-031137
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicentre cohort trial on acute appendicitis and microbiota, aetiology and effects of antimicrobial treatment: study protocol for the MAPPAC (Microbiology APPendicitis ACuta) trial

Abstract: IntroductionBased on the epidemiological and clinical data, acute appendicitis can present either as uncomplicated or complicated. The aetiology of these different appendicitis forms remains unknown. Antibiotic therapy has been shown to be safe, efficient and cost-effective for CT-confirmed uncomplicated acute appendicitis. Despite appendicitis being one of the most common surgical emergencies, there are very few reports on appendicitis aetiology and pathophysiology focusing on the differences between uncompli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
1
18
0
3
Order By: Relevance
“…and P. aeruginosa have also been shown to be a factor. [27,28] Our study was found to be compatible with the literature in this respect. It is difficult to explain the effects of these agents on infection, since the species identified in appendicitis were found to be compatible with the gastrointestinal microbiota, according to studies conducted with both new generation sequencing and culture methods.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…and P. aeruginosa have also been shown to be a factor. [27,28] Our study was found to be compatible with the literature in this respect. It is difficult to explain the effects of these agents on infection, since the species identified in appendicitis were found to be compatible with the gastrointestinal microbiota, according to studies conducted with both new generation sequencing and culture methods.…”
Section: Discussionsupporting
confidence: 91%
“…It is difficult to explain the effects of these agents on infection, since the species identified in appendicitis were found to be compatible with the gastrointestinal microbiota, according to studies conducted with both new generation sequencing and culture methods. [28] In addition, microbiota profiles vary from person to person. Although factors such as diet, geography, medicines (antibiotics, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two recent trial study protocols describe one trial planning to compare antibiotics with placebo for nonperforated appendicitis in adults and another trial designed to investigate microbiota and effects of antimicrobial treatment of appendicitis in adults. [35,36]…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Although not yet researched, the availability of metformin in the appendix 6 and the anti-inflammatory, anti-microbial and immune modulatory properties of metformin 7 , 8 could partly explain such a reduced risk. Gut immune-microbe interaction may play an important role in the development of acute appendicitis 21 and a prospective clinical trial investigating the relationship between gut microbiota and acute appendicitis is being conducted 22 . Fusobacteria infection has been linked to acute appendicitis 23 and Akkermansia muciniphila (a mucin-degrading bacterium that colonizes in the mucus layer and improves intestinal barrier function) 24 is inversely associated with the severity of acute appendicitis 23 .…”
Section: Discussionmentioning
confidence: 99%